DEWARUCI BOARD GAME DESIGN AS A WAYANG INTRODUCTION MEDIA FOR CHILDREN 10-12 YEARS OLD - Dewi, Fajrina Cahya (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
Wayang is one of the artistic heritages that contains various good teachings in life. But now, there are many young generation forgets about wayang, and don't even know it. Watching Wayang Shows all night long is hard for children, that's why an alternative media are made in the form of games that can be played by children to introduce Wayang characters..The process of working in designing board games includes: (1) Pre-Production, including data collection, goal setting, concept determination, (2) Production, including content design, sketching, digitization, layouting, and printing (3) Post Production. This study project has produced a dummy board game theme about Dewaruci, where in the game, the theme of characters and stories of Dewaruci can be introduced to children. The work of the study project is expected to help children to get to know the noble artistic heritage. In addition, this work can be a motivation and inspiration for other creators who create works with archipelago content.